Collaborative Teacher and Students Sebagai Realisasi Pembelajaran Inovatif - Herman Herman; Dumaris E Silalahi; Yanti Kristina Sinaga (Indonesia Berdaya, 2023)
This Community Service (PkM) aims to improve the quality of education based on activities carried out through learning that optimizes learning centered on collaboration between teachers and students. This PkM was held at RK Private Elementary School No. 4 on Jalan Kesatria in Pematang Siantar. This PkM is carried out based on the PkM method which is based on the method of education to the community. Education in PkM is realized through learning English in class VB at the elementary school. The PkM implementation went well according to the schedule set by the PkM Team and the school. The principal and teachers, especially the homeroom teacher for class VB, welcomed the implementation of this PkM well. In this PkM implementation, students respond actively. Learning activities occur in accordance with the expectation that teachers and students collaborate to understand and solve problems faced by students so that they can improve learning achievement, especially in learning English in accordance with predetermined learning objectives. So it can be concluded that the implementation of PkM brings innovation to learning English for elementary school students and also as a reference for teachers to implement innovative learning based on the 21st century in accordance with the development of education in Indonesia in order to achieve Indonesia's national education goals to create independent, innovative students and noble character